MultiDsk: A Ubiquitin-Specific Affinity Resin - Wilson, Marcus D.; Saponaro, Marco; Leidl, Mathias A.; Svejstrup, Jesper Q. (PLOS ONE, 2012)
Ubiquitylation is a highly diverse and complex post-translational modification for the regulation of protein function and stability. Studies of ubiquitylation have, however, been hampered by its rapid reversal in cell extracts, for example through the action of de-ubiquitylating enzymes (DUBs). Here we describe a novel ubiquitin-binding protein reagent, MultiDsk, composed of an array of five UBA domains from the yeast ubiquitin-binding protein Dsk2, fused to GST. MultiDsk binds ubiquitylated substrates with unprecedented avidity, and can be used as both an affinity resin to study protein ubiquitylation, and to effectively protect ubiquitylated proteins from the action of DUBs and the proteasome in crude cell extracts. We use the resin to show that the Def1 protein becomes ubiquitylated in response to DNA damage, and to isolate ubiquitylated forms of RNA polymerase II.